2020
DOI: 10.1038/s41598-020-72334-7
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective mapping of metastable states using electron-beam induced luminescence microscopy

Abstract: Metastable states created by electron or hole capture in crystal defects are widely used in dosimetry and photonic applications. Feldspar, the most abundant mineral in the Earth’s crust (> 50%), generates metastable states with lifetimes of millions of years upon exposure to ionizing radiation. Although feldspar is widely used in dosimetry and geochronometry, the creation of metastable states and charge transfer across them is poorly understood. Understanding such phenomena requires next-generation methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 50 publications
1
17
3
Order By: Relevance
“…Mauz et al, 2020) or are related to IR-RF characteristics of single feldspar grains. Kumar et al (2020) reported zoning of feldspar grains linked to the geochemical composition. On some of our images (not shown), it appears that the light is not evenly distributed over the grain surface.…”
Section: The Scientific Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mauz et al, 2020) or are related to IR-RF characteristics of single feldspar grains. Kumar et al (2020) reported zoning of feldspar grains linked to the geochemical composition. On some of our images (not shown), it appears that the light is not evenly distributed over the grain surface.…”
Section: The Scientific Dimensionmentioning
confidence: 99%
“…Buylaert et al (2018) unsuccessfully searched for a correlation between K concentration and the post-IR IRSL D e in single grains of K-feldspar. Recently,Kumar et al (2020) reported a correlation of the K concentration and the IR signal measured with cathodoluminescence. Spatially resolved RF measurements in combination with spatially resolved IRSL measurements may help to link both observations.…”
mentioning
confidence: 99%
“…The nearby 90 Sr / 90 Y β source shielding emits secondary X-ray photons (bremsstrahlung, cf. Liritzis and Galloway, 1990), which induce localised high signal events at the CCD chip upon impact. The result is images speckled with bright spots (see Fig.…”
Section: Equipmentmentioning
confidence: 99%
“…Dütsch and Krbetschek, 1997). Kumar et al (2020) reported zoning of feldspar grains linked to the geochemical composition. On some of our images (not shown), it appears that the light is not evenly distributed over the grain surface.…”
Section: The Application Dimensionmentioning
confidence: 99%
See 1 more Smart Citation